Students, Faculty, and Staff's Willingness to Pay for Emergency Texting. Issue 4 (1st October 2016) - Yabe, Manako
ABSTRACT: Although emergency texting benefits callers' safety during violent situations and campus shooters, the service had not been popularized at a public university. To introduce emergency texting, this study proposed to identify the economic benefits of emergency texting and used the contingent valuation method which estimates students, faculty, and staff's willingness to pay for emergency texting. Despite the small sampling size, the total values of the three groups' willingness to pay were $7, 736 per year, larger than the lowest implementation costs of text-to-911. The estimation of the overall university population's total values may be expected to be greater than the results.